Implementation of iPad-based digital classroom services at al Azhar Islamic school 21 Solo Baru, Central Java, Indonesia - Dzulqornain, Khilmi; Narimo , Sabar; Wafroturrohmah , Wafroturrohmah; Haryanto , Sigit; Muhibbin , Ahmad (Universitas Ahmad Dahlan, 2023)
The need for digital innovation in the educational paradigm is increasingly clear after the Covid-19 phenomenon. This has also been strengthened by government policies in responding to this need, by launching “kurikulum merdeka” that demands the use of “merdeka mengajar” platform with all its characteristics. The concept of digital learning with a variety of devices is offered. SMP Islam Al Azhar 21 Solo Baru has implemented a program that is quite progressive in an effort to find an education digitalization system. It is in the form of digital class services, which can be used as an option for students and parents to carry out all digital-based and e-learning activities. Furthermore, the digital system used is relatively new and not many are used in Indonesia. The use of iPad 1:1 (every 1 student uses 1 iPad) as the main device with various Apple for education applications integrated in it. Regarding to this implementation, there is an interest from the researcher for further research related to its implementation. This type of research is descriptive qualitative which reports on how the school’s role in implementing iPad and its functions and contributions to classroom learning. The description regarding this matter was developed based on the results of semi-structured interviews and non-participant observations to see how this implementation could be carried out. Student group interviews were also used to support the findings. The result is an overview of the iPad-based digital classroom implementation starting from the initial ideas, the stages and steps of implementation, the perceptions of students and teachers, and the evaluation of those implementation. On the other hand, the main challenge lies in the relatively high budget requirements, and parents' doubts about the bad consequences of excessive iPad use, both in terms of health and social behavior